Evaluating User Satisfaction in Institutional Repositories through a Combined WebQual 4.0, EUCS, and Importance–Performance Analysis Approach - Putra, Syopiansyah Jaya; Nurazza, Abdullah Fadli; Arham, Zainul; Durachman, Yusuf; Waspodo, Bayu; Khalil, Ismail (Applied Information System and Management (AISM), 2026)
The repository website of UIN Syarif Hidayatullah Jakarta was designed to provide open access to academic publications produced by students and faculty members. However, it continues to encounter issues concerning interface usability, information accuracy, service personalization, and data access speed. These challenges underscore the necessity for a comprehensive assessment of its quality and the level of user satisfaction. This study aims to identify the key factors influencing user satisfaction, measure overall website performance through the WebQual Index (WQI), and analyze the alignment between user perceptions and expectations using the Importance Performance Analysis (IPA). A quantitative approach was employed, applying the extended WebQual 4.0 model with the inclusion of accuracy and timeliness variables adapted from the End-User Computing Satisfaction (EUCS) framework. Data were collected from 402 undergraduate respondents and analyzed using SPSS through validity, reliability, partial t-tests, and paired sample t-tests. The findings reveal that all independent variables significantly affect user satisfaction, and the website achieved a WQI score of 0.80, indicating a very good quality level. Nevertheless, aspects such as visual appeal and service personalization require improvement. The gap analysis result of 0.35 signifies that current performance has yet to fully meet user expectations. Furthermore, the IPA quadrant mapping provides strategic insights, emphasizing the need to enhance data security and the timeliness of information delivery. This research contributes to both theory and practice by developing an integrated evaluation framework that combines WebQual 4.0, EUCS, and IPA, offering a structured model for assessing user satisfaction within digital academic repositories in higher education institutions.